Fueling the Gilded Age : Railroads, Miners, and Disorder in Pennsylvania Coal Country - Arnold, Andrew Bernard (Book collections on Project MUSE., 2014)
If the railroads won the Gilded Age, the coal industry lost it. Railroads epitomized modern management, high technology, and vast economies of scale. By comparison, the coal industry was embarrassingly primitive. Miners and operators dug coal, bought it, and sold it in 1900 in the same ways that they had for generations. In the popular imagination, coal miners epitomized anti-modern forces as the so-called ""Molly Maguire"" terrorists. Yet the sleekly modern railroads were utterly dependent upon the disorderly coal industry. Railroad managers demanded that coal operators and miners acc